The Synchrotron Low-Energy Spectrum Arising from the Cooling of Electrons in Gamma-Ray Bursts - Panaitescu, A D; Vestrand, W T (arXiv.org, 2022)
This work is a continuation of a previous effort (Panaitescu 2019) to study the cooling of relativistic electrons through radiation (synchrotron and self-Compton) emission and adiabatic losses, with application to the spectra and light-curves of the synchrotron Gamma-Ray Burst produced by such cooling electrons. Here, we derive the low-energy slope b_LE of GRB pulse-integrated spectrum and quantify the implications of the measured distribution of b_LE. If the magnetic field lives longer than it takes the cooling GRB electrons to radiate below 1-10 keV, then radiative cooling processes of power P(gamma) ~ gamma^n with n geq 2, i.e. synchrotron and inverse-Compton (iC) through Thomson scatterings, lead to a soft low-energy spectral slope b_LE leq -1/2 of the GRB pulse-integrated spectrum F_eps ~ eps^{b_LE} below the peak-energy E_p, irrespective of the duration of electron injection t_i. IC-cooling dominated by scatterings at the Thomson--Klein-Nishina transition of synchrotron photons below E_p has an index n = 2/3 -> 1 and yield harder integrated spectra with b_LE in [0,1/6], while adiabatic electron-cooling leads to a soft slope b_LE = -3/4. Radiative processes that produce soft integrated spectra can accommodate the harder slopes measured by CGRO/BATSE and Fermi/GBM only if the magnetic field life-time t_B is shorter than the time during which the typical GRB electrons cool to radiate below 1-10 keV, which is less than (at most) ten radiative cooling timescales t_rad of the typical GRB electron. In this case, there is a one-to-one correspondence between t_B and b_LE. To account for low-energy slopes b_LE > -3/4, adiabatic electron-cooling requires a similar restriction on t_B. In this case, the diversity of slopes arises mostly from how the electron-injection rate varies with time and not from the magnetic field timescale.